Respuesta :

Answer:

c = 3[tex]\sqrt{6}[/tex]

Step-by-step explanation:

triangle is right isosceles so both sides equal 3[tex]\sqrt{3}[/tex]

can use pythagorean theorem which is square each leg and set it equal to the hypotenuse (side 'c') squared

(3[tex]\sqrt{3}[/tex])^2 +  (3[tex]\sqrt{3}[/tex])^2 = c^2

(9x3) + (9x3) = c^2

27 + 27 = c^2

54 = c^2

c = [tex]\sqrt{54}[/tex]

simplify  [tex]\sqrt{54}[/tex] to equal = [tex]\sqrt{9}[/tex] x [tex]\sqrt{6}[/tex] which simplies to 3[tex]\sqrt{6}[/tex]

ACCESS MORE